2013
DOI: 10.1128/cvi.00009-13
|View full text |Cite
|
Sign up to set email alerts
|

Case-Control Study of the Effectiveness of the 2010-2011 Seasonal Influenza Vaccine for Prevention of Laboratory-Confirmed Influenza Virus Infection in the Korean Adult Population

Abstract: We evaluated the effectiveness of the 2010-2011 seasonal influenza vaccine for preventing laboratory-confirmed influenza in a South Korean population. A retrospective case-control study was conducted among patients who visited selected hospitals from September 2010 to May 2011. A total of 483 laboratory-confirmed influenza patients were included in the analysis as case subjects. For each case patient, two types of control patients were chosen at a ratio of 1:1:1, and 966 control subjects were selected. Vaccine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…In addition, the vaccine did not demonstrate a statistically significant effectiveness for preventing influenza-related complications, including pneumonia, hospitalization or death. This finding was different from a previous study performed during the 2010–2011 season [ 8 ]. The main circulating influenza strain in the 2010–2011 season was the A/H1N1 2009pdm virus.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In addition, the vaccine did not demonstrate a statistically significant effectiveness for preventing influenza-related complications, including pneumonia, hospitalization or death. This finding was different from a previous study performed during the 2010–2011 season [ 8 ]. The main circulating influenza strain in the 2010–2011 season was the A/H1N1 2009pdm virus.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, to minimize the false negative results, control participants were restricted to patients who visited the same hospital with ILI within 48 hours of symptom onset. This type of control was proven to be appropriate in the previous study [ 8 ]. This method of control selection might cause another type of bias.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the Spanish influenza surveillance system reported low VE in seasons with predominant circulation of influenza A/H3N2 (14). Similarly, in the ROK, circulation of influenza A/H3N2 was dominant in the past 3 years, with reportedly low influenza VE (15,16). Of note, this study showed that influenza vaccination would be beneficial for elderly individuals and those with comorbidities despite statistically insignificant influenza VE.…”
Section: Discussionmentioning
confidence: 90%
“…The case-control design is the cost-effective and rapid way of the VE assessment during epidemic situation [10]. Previously case control study designs have been used in the post-licencing effectiveness of the oral cholera vaccine, rota virus vaccine and the influenza vaccines [13][14][15]. The case control design has already been adopted by studies from other countries for the COVID-19 VE assessment [16][17][18].…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%